PENGARUH DOSIS DAN LAMA PERLAKUAN EKSTRAK DAUN KALIANDRA MERAH (Calliandra calothyrsus Meissn.) TERHADAP STRUKTUR HISTOLOGI GINJAL MENCIT (Mus musculus L.) - Assiam, Nur; Setyawati, Iriani; Sudirga, Sang Ketut (SIMBIOSIS; Vol 2 No 2 (2014), 2014)
This research aims to determine the effect of red calliandra (Calliandra calothyrsus Meissn.) leaf extrac on the histological structure of the kidney of mice (Mus musculus L.). Treatment was administered orally with varying doses. This research used a Completely Randomized Design in factorial pattern of two factors, doses (0 or control, 2, 4, and 6 mg/kg BW) and length of treatment (7, 14, and 21 days), so there are 12 combination groups with 3 replications of each. Organ was collected on days 8, 15, and 22 to observe histological structure of the kidney. Renal histological observation of edema, Bowman’s space constriction, and protein deposition, showed no correlation between both factors, but a very real correlation occurs in the damage of fatty degeneration, hemorrhage, and nucleus pyknotic. Histological observation of glomerular congestion and infiltration of inflammatory cells did not show any correlation between dose and duration of treatment. Keywords: red calliandra, histopathology of kidney, male mice